The level of preparedness of prisoners for compensation to victims - Agnieszka Lewicka-Zelent (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
Over the centuries, the views on rehabilitation adults have been changing. The retributive justice paradigm began to be accompanied by another based on the principles of restorative justice, in which restoration is the main ingredient. Due to inadequate research in this field, the aim of the study was to determine the level of preparedness of prisoners for compensation to victims. The main research question was: "What level of readiness to redress emotionally materially and through services do the prisoners?" For this purpose a diagnostic survey method was employed as well as an own Redress Readiness Scale. The performed statistical analyses led to the conclusion that prisoners have significant deficits in readiness to restitution to injured persons.